(3GdSajfIs - (3CMeO Hf eMeO Hf MSjf Hf EHQGgje GHf SdjeGf, TgGH GdOjf GdeYQha HGHf eHGQc TGg,J (B862 (3g` s
(3ChdgG (B:s
(3McGjI Yf Gdbefi ef YdeGA GdTGaYjI HeUQ s
(3BNQgG (B:s
(3McGjI Yf QLd SeY fbQ GdOa aUGM hZTj Ydjg s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B229 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B56s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B483 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs